2022
DOI: 10.3390/ijms231810452
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Identifies Molecular Players and Biological Processes Specific to SARS-CoV-2 Exposure in Endothelial Cells

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been responsible for the severe pandemic of acute respiratory disease, coronavirus disease 2019 (COVID-19), experienced in the 21st century. The clinical manifestations range from mild symptoms to abnormal blood coagulation and severe respiratory failure. In severe cases, COVID-19 manifests as a thromboinflammatory disease. Damage to the vascular compartment caused by SARS-CoV-2 has been linked to thrombosis, triggered by an enhanced immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…4A). However, in line with previous evidence [33][34][35][36], in all the experimental conditions we failed to detect viral proteins at intracellular level (Fig. 4B).…”
Section: Exogenous α-Syn Monomers and Ifn-β Oppositely Modulate Sars-...supporting
confidence: 92%
See 1 more Smart Citation
“…4A). However, in line with previous evidence [33][34][35][36], in all the experimental conditions we failed to detect viral proteins at intracellular level (Fig. 4B).…”
Section: Exogenous α-Syn Monomers and Ifn-β Oppositely Modulate Sars-...supporting
confidence: 92%
“…Next, we sought to investigate whether the impaired α-syn multimerization observed in virus-susceptible epithelial cells occurs also in experimental models featuring non-productive SARS-CoV-2 infection. To such an aim, human endothelial umbilical vein cells (HUVECs) were used, as they have been widely documented to express very low levels of the SARS-CoV-2 receptor ACE2 and the protease TMPRSS2, which restrains their capacity for productive viral infection [33][34][35][36]. Initial results showed a time-related increase in SARS-CoV-2 N gene mRNA expression in HUVECs supernatants (Fig.…”
Section: Exogenous α-Syn Monomers and Ifn-β Oppositely Modulate Sars-...mentioning
confidence: 99%
“…In human umbilical vein endothelial cells (HUVECs), ProT is overexpressed under hypoxic conditions 43 or after viral infection. 44 Interactions of endothelial cells and PLTs are important for developing dengue complications. Thus, overexpression of ProT in endothelial cells may contribute not only to increased PLT clearance, thereby reducing PLT numbers, but also to extended bleeding times in ProT Tg mice.…”
Section: Discussionmentioning
confidence: 99%
“…Proteome analysis confirmed a dramatic remodeling of SARS-CoV-2-infected HL-mECs, whereas inhibition of Spike RGD/integrins interaction resulted in blocking SARS-CoV-2 infection and in a complete recovery of viral-induced HL-mEC dysfunction [ 20 , 21 ]. More recently, other studies confirmed the capability of SARS-CoV-2 to infect different ECs [ 59 , 60 , 61 ] and defined the role of vimentin [ 62 ] and heparan sulfates [ 63 ] in maintaining and increasing the binding affinity of the viral Spike protein to the EC surface, facilitating SARS-CoV-2 entry.…”
Section: Discussionmentioning
confidence: 99%